Energy transfer and thermal transport for unsteady fractional viscous fluid under Fourier and statistical analysis - Ibrahim Mahariq; Kashif Ali Abro; Ambreen Siyal (Propulsion and Power Research)
An energy transference from unsteady flow of the incompressible viscous fluid is proposed with radiative heat flux. In order to develop an efficient mathematical model, Rosseland estimation and Boussinesq approximation have been employed. An efficient mathematical model for energy transfer from unsteady flow of viscous fluid is established by means of newly presented fractional differential operator. The fractional differential operator has the capability to describe memory for energy transfer and hereditary properties based on its kernel for minimization or maximization of thermal performance within thermophysical features. The developed model for unsteady flow of viscous fluid is investigated for velocity, concentration and temperature via Fourier and statistical approaches. The analytical results have been simulated for the rheological parameters and statistical results are depicted for different types of graphs for knowing identical and proportional quantity of energy transference.